Eating bitterness : stories from the front lines of China's great urban migration - Loyalka, Michelle Dammon, 1972- (University of California Press, 2012)
Every year over 200 million peasants flock to China's urban centers, providing a profusion of cheap labor that helps fuel the country's staggering economic growth. Award-winning journalist Michelle Dammon Loyalka follows the trials and triumphs of eight such migrants-including a vegetable vendor, an itinerant knife sharpener, a free-spirited recycler, and a cash-strapped mother-offering an inside look at the pain, self-sacrifice, and uncertainty underlying China's dramatic national transformation. At the heart of the book lies each person's ability to "eat bitterness"--A term that roughly means to endure hardships, overcome difficulties, and forge ahead. These stories illustrate why China continues to advance, even as the rest of the world remains embroiled in financial turmoil. At the same time, "Eating Bitterness" demonstrates how dealing with the issues facing this class of people constitutes China's most pressing domestic challenge